Teachers' educational mediation and the role of benevolence in the fight against early school leaving - Line Numa-Bocage (University of Bologna, 2021)
The benevolent relationship that a teacher has with a pupil fosters the acquisition of knowledge. A relationship of this kind is not always easy to establish. Benevolence in teaching requires a pupil to be considered as a whole. This attention to the pupil is one of the dimensions of educational mediation. This article examines the taking into consideration of the pupil in school interactions. Thus, the concept of mediation represents all the learning aids used by teachers and is organised around the interaction between (teachers' and pupils') schemas (Numa-Bocage, 2007). It requires a benevolent stance on the part of the teachers which in turn makes it possible to fight against dropping out of school. Four examples of secondary-school research illustrate the benevolent dimension in mediation: using a game for the purposes of inclusive education; using self-confrontation in a group of students for the purpose of developing teaching practices; videorecording and the importance of taking into account what young people have to say; and listening and paying attention to young apprentices during the Covid-19 pandemic. Ways to fight dropping out are identified.